Self-Expandable Metallic Stent Implantation Combined With Bronchial Artery Infusion Chemoembolization in the Treatment of Lung Cancer With Complete Atelectasis - Li, Xiaobing; Yin, Meipan; Xie, Pengfei; Liu, Ying; Li, Xiangnan; Qi, Yu; Ma, Yaozhen; Li, Chunxia; Wu, Gang (Frontiers in Oncology, 2022)
Background Atelectasis is a common complication of lung cancer, and there are few reports about the treatment methods. This study retrospectively analyzed the safety and effectiveness of endotracheal metal stent implantation combined with arterial infusion chemoembolization in the treatment of non-small cell lung cancer with complete atelectasis. Methods The clinical data of patients with non-small cell lung cancer and complete atelectasis treated by self-expandable metallic stent implantation combined with arterial infusion chemotherapy were retrospectively analyzed. The clinical efficacy was evaluated and postoperative adverse reactions were observed. Progression-free survival and overall survival were analyzed by Kaplan-Meier method. Results In all, 42 endotracheal metallic stents were implanted in 42 patients under fluoroscopy. 5–7 days after stent implantation, CT showed that 24 patients (57.1%) had complete lung recruitment, and that 13 (31.0%) had partial lung recruitment. The technical success rate was 100%, and the clinical success rate was 88.1% (37/42). 5–7 days after stent implantation, bronchial artery infusion chemoembolization was performed in all patients. The median progression-free survival and overall survival were 6 months (95% CI: 2.04-9.66) and 10 months (95% CI: 7.22-12.79), respectively. Conclusion Self-expandable metallic stent implantation combined with arterial infusion chemoembolization may be an effective and safe strategy in the treatment of lung cancer with atelectasis clinically.